2004
DOI: 10.1002/marc.200490029
|View full text |Cite
|
Sign up to set email alerts
|

Cover Picture: Macromol. Rapid Commun. 15/2004

Abstract: Cover: The structure of pristine protonated layered titanate (HTO) (left) and the bright-field transmission electron microscopy image of a photodegradable nanocomposite (right) prepared by melt extrusion of polylactide and organically modified HTO are shown on the cover.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2006
2006
2010
2010

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 0 publications
0
27
0
Order By: Relevance
“…[40] For the same purpose, the addition of a layered titanate as nanofiller in the PLA matrix results in an enhanced rate of biodegradation under solar irradiation because of its photocatalytic reactivity, which is comparable to that of TiO 2 . [41] In this context, novel approaches based on clay-TiO 2 systems prepared by controlled deposition of TiO 2 nanoparticles on silicate surfaces can be envisaged.…”
Section: Green Bionanocompositesmentioning
confidence: 99%
“…[40] For the same purpose, the addition of a layered titanate as nanofiller in the PLA matrix results in an enhanced rate of biodegradation under solar irradiation because of its photocatalytic reactivity, which is comparable to that of TiO 2 . [41] In this context, novel approaches based on clay-TiO 2 systems prepared by controlled deposition of TiO 2 nanoparticles on silicate surfaces can be envisaged.…”
Section: Green Bionanocompositesmentioning
confidence: 99%
“…[4,5] The layer titanate (HTO) is a new nano-filler having high-surface charge density [4] compared with conventional layered silicates. Their names, chemical formula, and designations (as written in the text) are presented in Table 1.…”
Section: Experimental Partmentioning
confidence: 99%
“…[4,5] The nano-structure analyses of wide-angle X-ray diffraction (WAXD) and transmission electron microscopy (TEM) were carried out using the same apparatus as in the previous articles. [3][4][5] Here we briefly describe molecular modeling of the intercalants. By aid of computer simulation, we proposed the molecular dimensions of two different intercalants using the molecular dynamics program (MM2 in Quantum CAChe, Fujitsu Ltd.) in consideration of van der Waals radi.…”
Section: Experimental Partmentioning
confidence: 99%
See 1 more Smart Citation
“…Very recently, Hiroi and Okamoto et al 86 first reported the photodegradability of neat PLA and corresponding Figure 34 shows the UV/VIS transmission spectra of pure PLA and nanocomposite (PLANC1 . 7).…”
Section: Photodegradationmentioning
confidence: 99%